A novel method to determine flow‐accelerated corrosion rate based on fluid structure interaction. Issue 11 (7th May 2013) - Zhu, X. L.; Zhu, L. X.; Lu, X. F.; Ling, X.
<x xml:space="preserve">Abstract</x> In this paper, the mechanism of flow‐accelerated corrosion (FAC) and FAC rate prediction model are investigated. A modified MIT model is obtained by illustrating the relationship between CPF thickness and porosity with CPF stress based on fluid structure interaction (FSI) numerical simulation. The results reveal that the effect of fluid on CPF strength gradually increased with increasing of velocity, thereby increasing Tresca stress and deformation. CPF thickness gradually decreased with increasing stress and decreasing pH. CPF porosity gradually increased with increasing Tresca stress; however, porosity change became smaller when stress reached a certain value. CPF porosity is gradually reduced with increasing temperature. Finally, FAC rate is proportional to Tresca stress and temperature and is inversely proportional to pH. The calculation results of the modified MIT model agree with the experimental results.